Bioinspired Alkenyl Amino Alcohol Ionizable Lipid Materials for Highly Potent In Vivo mRNA Delivery. Issue 15 (18th February 2016) - Fenton, Owen S.; Kauffman, Kevin J.; McClellan, Rebecca L.; Appel, Eric A.; Dorkin, J. Robert; Tibbitt, Mark W.; Heartlein, Michael W.; DeRosa, Frank; Langer, Robert; Anderson, Daniel G.
Abstract : Thousands of human diseases could be treated by selectively controlling the expression of specific proteins in vivo . A new series of alkenyl amino alcohol (AAA) ionizable lipid nanoparticles (LNPs) capable of delivering human mRNA with unprecedented levels of in vivo efficacy is demonstrated. This study highlights the importance of utilizing synthesis tools in tandem with biological inspiration to understand and improve nucleic acid delivery in vivo.